Revision of the Early Ordovician (late Tremadocian; Stairsian) cheirurid trilobite Tesselacauda Ross, with species from the Great Basin, western USA - Adrain, Jonathan M.; Karim, Talia S. (Zootaxa, 2019)
The Stairsian genus Tesselacauda Ross, 1951, has historically included two species, the poorly known type, T. depressa Ross, 1951 (Bearriverops loganensis Zone), and the even less well known T. flabella Kobayashi, 1955 (Bearriverops alsacharovi Zone), which may not belong to the genus. The family assignment of the genus has long been in question, with some workers assigning it to Cheiruridae and some to Pliomeridae. New field collections from western Utah and southeastern Idaho yield abundant material of T. depressa, which facilitates revision on the basis of multiple specimens of most exoskeletal parts. Two additional well known species are proposed, T. morrisoni (Rossaspis leboni Zone), and T. kriegerae (Bearriverops alsacharovi Zone). A third new species, very similar to T. depressa, is described in open nomenclature from the Rossaspis leboni Zone. Knowledge of hypostomes from silicified material helps to clarify the basal morphologies of cheirurid versus pliomerid trilobites. Pliomerids have anteroposteriorly elongate hypostomes with a basic pattern of three pairs of lateral hypostomal spines and a single posteromedian spine. Some or all of the spines are reduced or lost in various taxa. Cheirurids either lack paired spines or have only one or two pairs, and never have a posteromedian spine. Cheirurid hypostomes tend to be much shorter and more subquadrate than pliomerids. Other differences between the families are: a small, triangular or trapezoidal rostral plate in pliomerids versus a wide, short plate in cheirurids; a thoracic segment count commonly of 11–13 in Cheiruridae (fewer in one derived subfamily) versus commonly 15 or more in pliomerids (fewer in two derived subfamilies); thoracic pleurae with subequal bands and a prominent furrow in cheirurids versus a much more inflated and rib-like posterior band, reduced anterior band, and short, anteriorly placed furrow; and pygidia with four or fewer segments in cheirurids versus commonly five in pliomerids (again, fewer in two derived subfamilies). On these and other criteria, Tesselacauda is clearly a cheirurid, assigned for the present to the presumptively basal and possibly paraphyletic Subfamily Pilekiinae.